Land degradation in the developing world: implications for food, agriculture, and the environment to 2020 - Scherr, Sara J.; Yadav, Satya N. (International Food Policy Research Institute, 1996)
By the year 2020 land degradation may pose a serious threat to food production and rural livelihoods, particularly in poor and densely populated areas of the developing world. Appropriate policies are required to encourage land-improving investments and better land management if developing countries are to sustainably meet the food needs of their populations. The authors investigate the impact of land degradation on global agricultural production.However, land degradation could have dramatic effects in specific countries and subregions in the form of (1) Nutrient depletion; (2) Salinization; (3) Agrochemical pollution; (4) Soil erosion; (5) Vegetative degradation of rangelands and ; (6) Agriculture-induced deforestation by 2020. The brief identifies strategies to reduce land degradation. and makes policy recommendations.